Integration of buprenorphine/naloxone treatment into HIV clinical care: lessons from the BHIVES collaborative. - Weiss, Linda; Netherland, Julie; Egan, James E; Flanigan, Timothy P; Fiellin, David A; Finkelstein, Ruth; Altice, Frederick L (Journal of acquired immune deficiency syndromes (1999), 2011)
Replication of effective practices requires detailed descriptions of implementation processes, barriers and facilitators, and lessons learned. The experiences of physicians leading the Buprenorphine HIV Evaluation and Support initiative provides valuable information for other HIV providers seeking to integrate medication-assisted treatment services into HIV clinical care.
Keywords: Ambulatory Care; Anti-HIV Agents; Buprenorphine; Delivery of Health Care, Integrated; Health Resources; Health Services Needs and Demand; HIV Infections; Humans; Naloxone; Narcotic Antagonists; Opiate Substitution Treatment; Opioid-Related Disorders; Primary Health Care; Substance Abuse Treatment Centers; United States